2009
DOI: 10.1017/s0007114509990778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of l-carnitine on metabolism and performance of sows

Abstract: In recent years, L-carnitine has been used increasingly as a supplement in livestock animals. The present review gives an overview of the effects of dietary L-carnitine supplementation on the reproductive performance of sows. Results concerning the effect of L-carnitine supplementation during pregnancy on litter sizes are controversial. There are some studies reporting an increased number of piglets born alive per litter, while others could not find such an effect. In contrast, most studies performed show cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 99 publications
0
11
0
2
Order By: Relevance
“…It has been assumed that these effects of carnitine were mediated by influencing the secretion of IGF-1 and insulin and by an increased intrauterine nutrition of fetuses [24,25,28]. In contrast, supplementation of carnitine during lactation had less effects on sow and litter performance [22,24].…”
Section: Resultsmentioning
confidence: 99%
“…It has been assumed that these effects of carnitine were mediated by influencing the secretion of IGF-1 and insulin and by an increased intrauterine nutrition of fetuses [24,25,28]. In contrast, supplementation of carnitine during lactation had less effects on sow and litter performance [22,24].…”
Section: Resultsmentioning
confidence: 99%
“…). In these animals, L‐carnitine improve reproductive performance by mobilizing more energy from different tissues such as adipose tissues (Eder ).…”
Section: The Physicochemical Properties Of L‐carnitine and Its Generamentioning
confidence: 99%
“…, ), most previous reviews have mainly concentrated on application and dosage of L‐carnitine in aquatic animal diets (Liu & Zhu ; Harpaz ; Ozório ; Li ). Previous reviews in vertebrates have indicated indispensable functions of L‐carnitine in intermediary energy metabolism in sows (Eder ), pigs (Li & Li ), dogs (Dove ), humans (Venkataraman ; Pekala et al . ; Vidal‐Casariego et al .…”
Section: Introductionmentioning
confidence: 99%
“…Eder (5) beschreibt in seinem Übersichtsartikel den Einfluss von Carnitin auf den Stoffwechsel und die Leistung von Sauen. Die festgestellten positiven Effekte von Carnitin auf die Zahl der lebend geborenen Ferkel pro Wurf und damit auch auf die Totgeburtenrate, auf die Geburtslebendmasse sowie auf die Zunahmen in der Säugezeit beruhen jedoch in allen Untersuchungen auf einer Carnitinsupplementierung des Futters tragender und/oder laktierender Sauen.…”
Section: Einleitung Und Fragestellungunclassified